ABS quantum dot diffusion plate and preparation method thereof
By using ABS resin and surface-modified CdSe quantum dots, combined with additives and three-layer coextrusion structure, the problem of insufficient mechanical properties and weatherability of existing quantum dot diffusion plates is solved, and high thermal stability, strong mechanical properties and stability are achieved A new quantum dot diffusion plate with optical performance.
Patent Information
- Application Number
- CN202410378217.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-29
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-03-29
AI Technical Summary
The substrate of existing quantum dot diffusion plates is mainly general-grade polystyrene (GPPS), which leads to deterioration of its mechanical properties, low thermal deformation temperature, poor heat resistance, easy softening and deformation, poor anti-aging ability, easy yellowing and cracking, Poor dispersion leads to large fluctuations in color points.
ABS resin is used as the matrix material, and surface-modified CdSe quantum dots are prepared by heat injection method, and combined with additives such as antioxidants, ultraviolet absorbers, light stabilizers and mineral oils to form a diffusion plate with a three-layer coextruded structure.
It significantly improves the thermal stability, mechanical strength, optical properties and weather resistance of the quantum dot diffusion plate, extends the service life and reduces color point fluctuations.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of quantum dot diffusion plates, and in particular to an ABS quantum dot diffusion plate and a preparation method thereof. Background Art
[0002] Quantum dots are widely used in quantum dot diffuser plates because of their excellent optical properties. However, the substrate of the finished quantum dot diffuser plates is currently mainly general-purpose polystyrene (GPPS). After the introduction of quantum dots, the mechanical properties of the single GPPS resin substrate are significantly deteriorated, especially in terms of low heat deformation temperature, poor heat resistance, and easy softening and deformation. At the same time, GPPS resin has poor anti-aging ability, is prone to yellowing and cracking, and due to the poor dispersion of quantum dots, it is easy to cause large color point fluctuations in the diffuser plate. In view of the above problems, it is urgent to develop a new type of quantum dot diffuser plate material with excellent performance. Summary of the invention
[0003] The present invention provides an ABS quantum dot diffusion plate and a preparation method thereof to solve the above technical problems.
[0004] The contents of the present invention are as follows;
[0005] The object of the present invention is to provide an ABS quantum dot diffusion plate, which is composed of an ABS resin matrix, quantum dots, and an additive, and includes an upper layer, a middle layer, and a lower layer, wherein:
[0006] The intermediate layer material components include the following raw materials in parts by weight: 100 parts of ABS resin, 0.01-1 parts of quantum dots, 0.1-2 parts of antioxidants, 0.1-2 parts of ultraviolet absorbers, 0.1-2 parts of light stabilizers, 0.1-1 parts of mineral oils, and 0.01-1 parts of brighteners;
[0007] The upper layer and the lower layer material components include the following raw materials in parts by weight: 100 parts of ABS resin, 0.01-1 parts of silicone resin, 0.1-2 parts of antioxidant, 0.1-2 parts of ultraviolet absorber, 0.1-2 parts of light stabilizer, 0.1-1 parts of mineral oil, and 0.01-1 parts of brightener.
[0008] Specifically, the quantum dots are CdSe quantum dots.
[0009] Specifically, the antioxidant is 2,6-di-tert-butyl-p-cresol.
[0010] Specifically, the ultraviolet absorber is UV-928.
[0011] Specifically, the light stabilizer is a composite hindered amine light stabilizer 770.
[0012] Specifically, the mineral oil is paraffin mineral oil.
[0013] Specifically, the brightener OB-1.
[0014] Specifically, the silicone resin is polydimethylsiloxane.
[0015] The above-mentioned method for preparing an ABS quantum dot diffusion plate comprises the following steps:
[0016] (1) putting the components of the middle layer and the upper and lower layers into a high-speed mixer according to the formula, and premixing them at a speed of 100-200 rpm for 5-15 minutes to obtain a middle layer mixture and an upper and lower layer mixture;
[0017] (2) adding the intermediate layer mixture into a twin-screw extruder, extruding, cooling, and pelletizing at a temperature of 190-220° C. and a rotation speed of 30-50 rpm to obtain an intermediate layer masterbatch;
[0018] (3) adding the upper layer mixture into a twin-screw extruder, extruding, cooling, and pelletizing at a temperature of 190-220° C. and a rotation speed of 30-50 rpm to obtain an upper layer masterbatch; the lower layer masterbatch is obtained by the same method;
[0019] (4) The middle layer masterbatch, the upper layer masterbatch and the lower layer masterbatch are added into three single screw extruders at a weight ratio of 50-80:10-20:10-20, and extruded through a three-layer co-extrusion die head at an extrusion temperature of 200-240°C and a screw speed of 20-60rpm to form a sheet, which is stretched and shaped by a traction roller and cut to obtain an ABS quantum dot diffusion plate, wherein the thickness of the middle layer is 0.2-3mm, and the thickness of the upper and lower layers is 0.1-0.5mm.
[0020] Compared with the prior art, the ABS quantum dot diffusion plate and its preparation method and its preparation method of the present invention can achieve the following beneficial effects:
[0021] 1. Selection of ABS resin matrix and synergistic effect. The present invention selects ABS resin as the matrix material of the quantum dot diffusion plate based on the following considerations: ABS is copolymerized from three monomers: acrylonitrile (A), butadiene (B) and styrene (S). The acrylonitrile structural unit gives the material excellent thermal stability, strength and rigidity; the butadiene structural unit provides good impact resistance; and the styrene structural unit brings processing fluidity and surface gloss. The three complement each other and synergize to make ABS have multiple excellent properties.
[0022] The ABS molecular chain contains unsaturated double bonds formed by butadiene structural units. After graft copolymerization modification, polar groups such as maleic anhydride or acrylic acid are added to the ABS molecular chain, which can greatly improve the compatibility between the ABS matrix and quantum dots and facilitate the dispersion of quantum dots. At the same time, the unsaturated double bonds introduced by graft copolymerization can also form a partial cross-linked structure, further improving the heat resistance and mechanical strength of the material.
[0023] 2. Interface strengthening effect between quantum dots and matrix. CdSe quantum dots are inorganic nanoparticles with high surface energy. Therefore, organic ligands such as oleic acid are required for surface modification during synthesis to improve their compatibility with organic matrices. In the present invention, the preparation of quantum dots adopts the hot injection method, using cadmium, selenium and oleic acid as raw materials. While reacting at high temperature to form CdSe quantum dots, oleic acid molecules are adsorbed on the surface of quantum dots through coordination, playing a role of dispersion and stabilization.
[0024] When quantum dots are blended with ABS matrix, the carboxyl groups in the oleic acid molecules can form hydrogen bonds with maleic anhydride or acrylic acid grafted on the ABS molecular chain, enhancing the interface bonding between the quantum dots and the matrix, inhibiting the aggregation of quantum dots, and improving the dispersibility and stability. At the same time, the long-chain alkyl structure of the oleic acid molecule can also increase the hydrophobicity and improve the dispersibility of the quantum dots in the ABS matrix.
[0025] 3. Synergistic and superposition effects between additives. Antioxidant BHT and hindered amine light stabilizer HALS-770 synergistically inhibit photo-oxidative aging. BHT is a phenolic primary antioxidant, and its phenolic hydroxyl group can capture free radicals generated during polymer aging and interrupt the auto-oxidative cycle reaction. HALS-770 is a composite hindered amine light stabilizer. Under light conditions, the methyl group on the piperidine ring can be converted into nitroxide free radicals, which can not only capture polymer free radicals, but also remove active species such as singlet oxygen. The two are used together to synergistically inhibit the photo-oxidative degradation of ABS resin from the two links of free radical generation and transmission, resulting in a synergistic effect of "1+1>2".
[0026] 4. UV absorber UV-928 and light stabilizer OB-1 work together to absorb UV light. UV-928 is a triazine type UV absorber that mainly absorbs medium and short-wave UV light of 290-350nm. OB-1 is an oxazoline derivative that mainly absorbs long-wave UV light below 400nm. The combination of the two can cover a wider UV band, block ABS resin and quantum dots from absorbing harmful UV light, and slow down photodegradation.
[0027] 5. The special design of the three-layer co-extrusion structure is a major innovation and highlight of the present invention. The upper and lower layers contain silicone and brightener, which can protect the optical properties of quantum dots while providing surface hardness and wear resistance. The middle layer relies on the fluorescence emission of quantum dots to produce a high-efficiency optical waveguide transmission effect. Under the wrapping of the upper and lower surface layers, the quantum dots are not easily oxidized and deactivated, and the optical properties are more stable and lasting.
[0028] In summary, the present invention forms a variety of synergistic effects between the components through systematic optimization in terms of material formula, preparation process, etc., and finally obtains a new ABS quantum dot diffusion plate with excellent performance. Compared with conventional quantum dot diffusion plates, thermal stability, mechanical strength, optical properties and weather resistance are significantly improved, showing many unexpected technical effects, reflecting the innovation of the present invention. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with the specific embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0030] The specific information of each component used in the present invention is as follows:
[0031] (1) ABS resin: trade name PA-758, MFR (220℃ / 10Kg) 34g / 10min, density 1.08g / cm 3 ;
[0032] (2) CdSe quantum dots: trade name PLxBead series, size 4-8 nm, absorption wavelength 500-640 nm, emission wavelength 520-650 nm, quantum yield ≥ 70%, dispersed in cyclohexane, concentration 50 mg / mL;
[0033] Key preparation points: Using the hot injection method, a mixture of cadmium, selenium, oleic acid, octadecene, and trioctylphosphine oxide is refluxed at high temperature, and the reaction time and temperature are controlled to regulate the size of the quantum dots; then the quantum dots are purified by precipitation with isopropanol, dispersed in cyclohexane, the concentration is adjusted to 50 mg / mL, and stored in a vacuum seal.
[0034] (3) Additives such as BHT, UV-928, and hindered amine light stabilizer 770 are conventional commercial products and can be purchased from many chemical reagent companies.
[0035] Example 1 An ABS quantum dot diffusion plate, the middle layer formula (weight parts): 100 parts of ABS resin, 0.01 parts of CdSe quantum dots, 0.1 parts of BHT, 0.1 parts of UV-928, 0.1 parts of HALS-770, 0.1 parts of mineral oil, and 0.01 parts of OB-1. The upper and lower layer formulas (weight parts): 100 parts of ABS resin, 0.01 parts of ST-1087, 0.1 parts of BHT, 0.1 parts of UV-928, 0.1 parts of HALS-770, 0.1 parts of mineral oil, and 0.01 parts of OB-1. Preparation method: The raw materials for the middle layer and the upper and lower layers are mixed in a high-speed mixer at 100 rpm for 5 minutes, extruded, cooled and pelletized at 190°C and 30 rpm in a twin-screw extruder to obtain a masterbatch; the masterbatch is added to a three-layer co-extruder in a ratio of 50:20:20, extruded at 200°C and 20 rpm, and cut into quantum dot diffusion plates with a thickness of 1.8 mm after traction cooling, the middle layer is 0.2 mm, and the upper and lower layers are each 0.1 mm.
[0036] Example 2 An ABS quantum dot diffusion plate, the middle layer formula (weight parts): 100 parts of ABS resin, 0.5 parts of CdSe quantum dots, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, 0.5 parts of OB-1. The upper and lower layer formulas (weight parts): 100 parts of ABS resin, 0.5 parts of ST-1087, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, and 0.5 parts of OB-1. Preparation method: The raw materials for the middle layer and the upper and lower layers are mixed in a high-speed mixer at 150 rpm for 10 min, extruded, cooled and pelletized at 200 ° C and 40 rpm in a twin-screw extruder to obtain a masterbatch; the masterbatch is added to a three-layer co-extruder in a ratio of 65:15:15, extruded at 220 ° C and 40 rpm, and cut into quantum dot diffusion plates with a thickness of 2 mm after traction cooling, the middle layer is 1.3 mm, and the upper and lower layers are 0.3 mm each.
[0037] Example 3 An ABS quantum dot diffusion plate, the middle layer formula (weight parts): 100 parts of ABS resin, 1 part of CdSe quantum dots, 2 parts of BHT, 2 parts of UV-928, 2 parts of HALS-770, 1 part of mineral oil, 1 part of OB-1. The upper and lower layer formula (weight parts): 100 parts of ABS resin, 1 part of ST-1087, 2 parts of BHT, 2 parts of UV-928, 2 parts of HALS-770, 1 part of mineral oil, 1 part of OB-1. Preparation method: The raw materials of the middle layer and the upper and lower layers are mixed in a high-speed mixer at 200rpm for 15min, extruded at 210℃ and 50rpm in a twin-screw extruder, cooled and pelletized to obtain a masterbatch; the masterbatch is added to a three-layer co-extruder at a ratio of 80:10:10, extruded at 240℃ and 60rpm, and cut after traction cooling to obtain a quantum dot diffusion plate with a thickness of 2.2mm, a middle layer of 2mm, and an upper and lower layer of 0.5mm each.
[0038] Comparative Example 1 (ABS resin replaced by GPPS) Middle layer formula (weight parts): 100 parts of GPPS resin, 0.5 parts of CdSe quantum dots, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, 0.5 parts of OB-1. Upper and lower layer formula (weight parts): 100 parts of GPPS resin, 0.5 parts of ST-1087, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, 0.5 parts of OB-1. The preparation method is the same as that of Example 2.
[0039] Comparative Example 2 (quantum dots replaced with ordinary fluorescent dyes) Middle layer formula (weight parts): 100 parts of ABS resin, 0.5 parts of fluorescent brightener OB, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, 0.5 parts of OB-1. Upper and lower layer formula (weight parts): 100 parts of ABS resin, 0.5 parts of ST-1087, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, 0.5 parts of OB-1. The preparation method is the same as that of Example 2.
[0040] Comparative Example 3 (reduced types of additives) Middle layer formula (weight parts): 100 parts of ABS resin, 0.5 parts of CdSe quantum dots, 1 part of BHT. Upper and lower layer formula (weight parts): 100 parts of ABS resin, 0.5 parts of ST-1087. The preparation method is the same as Example 2.
[0041] Comparative Example 4 (without upper and lower protective layers, single-layer structure) Intermediate layer formula (parts by weight): 100 parts of ABS resin, 0.5 parts of CdSe quantum dots, 1 part of BHT, 1 part of UV-928, 1 part of HALS-770, 0.5 parts of mineral oil, 0.5 parts of OB-1, and 0.5 parts of ST-1087. Preparation method: The raw materials are mixed in a high-speed mixer at 150 rpm for 10 minutes, extruded in a twin-screw extruder at 210°C and 40 rpm, cooled and pelletized to obtain a masterbatch; the masterbatch is added to a single-screw extruder, extruded at 220°C and 40 rpm, and cut into a quantum dot diffusion plate with a thickness of 2 mm after traction cooling.
[0042] Comparative Example 5 (too high dosage of additives) Middle layer formula (weight parts): 100 parts of ABS resin, 5 parts of CdSe quantum dots, 5 parts of BHT, 5 parts of UV-928, 5 parts of HALS-770, 5 parts of mineral oil, 5 parts of OB-1. Upper and lower layer formula (weight parts): 100 parts of ABS resin, 5 parts of ST-1087, 5 parts of BHT, 5 parts of UV-928, 5 parts of HALS-770, 5 parts of mineral oil, 5 parts of OB-1. The preparation method is the same as that of Example 2.
[0043] The formula of Comparative Example 6 (improper preparation parameters) is the same as that of Example 2, but the preparation method is different: the raw materials for the middle layer and the upper and lower layers are mixed in a high-speed mixer at 80 rpm for 3 min, respectively, and extruded, cooled and pelletized at 190°C and 20 rpm in a twin-screw extruder to obtain a masterbatch; the masterbatch is added to a three-layer co-extruder at a ratio of 90:5:5, extruded at 260°C and 80 rpm, and cut after traction cooling.
[0044] The following are the testing standards, methods and results of the embodiments and comparative examples:
[0045] 1. Heat Deformation Temperature: The temperature at which the specimen begins to deform is measured in °C at a load of 1.82 MPa and a heating rate of 2 °C / min in accordance with ASTM D648.
[0046] 2. Impact strength: According to ASTM D256 method, the cantilever beam impact strength of the notched specimen is measured using an cantilever beam impact testing machine, unit Kg-cm / cm.
[0047] 3. Haze: According to ASTM D1003 standard, use a haze meter to measure the percentage of diffuse reflected light of the sample to the total transmitted light.
[0048] 4. Light transmittance: According to ASTM D1003 standard, use the light transmittance test device attached to the haze meter to measure the total light transmittance of the sample.
[0049] 5. Color point: Use BYK Gardner colorimeter to measure the color point coordinates of the sample under D65 light source and 10° field of view.
[0050] 6. Weather resistance: According to ASTM G154 standard, the accelerated aging test was carried out in a UV aging test chamber. The cycle conditions were 8h UV irradiation (60℃), 4h condensation (50℃), and the light intensity was 0.89W / (m 2 ·nm), refers to the aging time for the sample to maintain more than 50% of its mechanical strength, in hours.
[0051] Test results summary table:
[0052]
[0053] Table 1
[0054] (1) In Examples 1-3, within the range of raw material formula and preparation parameters specified in the present invention, the quantum dot diffusion plates prepared have excellent comprehensive performance, and indicators such as heat deformation temperature, impact strength, haze, light transmittance, color point, and weather resistance perform well, which can basically meet the actual application requirements.
[0055] (2) Comparative Example 1 uses GPPS to replace ABS resin, resulting in a significant decrease in heat deformation temperature and impact strength. This is because GPPS has a regular molecular chain structure and lacks the toughness provided by the butadiene structural unit in ABS.
[0056] (3) In Comparative Example 2, quantum dots are replaced by fluorescent dyes. Although the transmittance does not change much, the haze is significantly reduced and the color point increases significantly, indicating that the luminous efficiency and color purity of fluorescent dyes cannot be compared with those of quantum dots.
[0057] (4) The types of auxiliary agents in comparative example 3 are incomplete, resulting in a decrease in mechanical properties, haze transmittance and weather resistance, indicating that the auxiliary agents of the present invention have a synergistic effect and none of them can be missing.
[0058] (5) Comparative Example 4 has no upper and lower protective layer structure. Although the mechanical properties, haze, etc. do not change much, the overall optical properties are reduced and the weather resistance is also weakened.
[0059] (6) In comparative example 5, the amount of additives used was too high, and various properties were reduced. This is because the excessive amount of additives introduced impurities, destroyed the interface between the quantum dots and the matrix, caused the quantum dots to agglomerate, and reduced the optical properties. At the same time, the high amount of additives will also inhibit the movement of the ABS molecular chain and reduce the mechanical strength. It can be seen that the amount of additives needs to be strictly controlled.
[0060] (7) Comparative Example 6 was not prepared according to the preferred preparation parameters of the present invention, and the mixing uniformity and molding quality were poor, resulting in unsatisfactory overall performance of the diffuser plate.
[0061] As can be seen from the above table, the best embodiment of the present invention is Example 3, and its raw material ratio and preparation process parameters are as follows: middle layer formula (weight parts): ABS 100 parts, CdSe quantum dots 1 part, BHT 2 parts, UV-928 2 parts, HALS-770 2 parts, mineral oil 1 part, OB-1 1 part; upper and lower layer formula (weight parts): ABS 100 parts, ST-1087 1 part, BHT 2 parts, UV-928 2 parts, HALS-770 2 parts, mineral oil 1 part, OB-1 1 parts; preparation method: the middle layer and upper and lower layer raw materials are mixed in a high-speed mixer at 200rpm for 15min, and mixed in a twin-screw extruder at 190°C and 50rpm for 15min to obtain a masterbatch; the masterbatch is added to a three-layer co-extruder at a ratio of 80:10:10, and extruded at 240°C and 60rpm to obtain a 2.2mm thick sheet.
[0062] Combined with the test results, the present invention has the following unexpected technical effects:
[0063] 1. The interfacial compatibilization between quantum dots and ABS matrix brings about a significant improvement in mechanical properties. The oleic acid ligands on the surface of CdSe quantum dots and the maleic anhydride / acrylic acid on the ABS molecular chain undergo a dipole-dipole interaction, which not only enhances the dispersion of quantum dots and improves the transmittance, but also forms a nano-scale dispersed phase structure, which is equivalent to a "nano buffer" that absorbs external forces, greatly improving the impact toughness of the diffusion plate, and the heat deformation temperature is also increased from 85°C of GPPS to above 112°C.
[0064] 2. The rapid energy transfer effect of quantum dots brings about a leap in optical performance. Quantum dots have an adjustable band gap, a narrow emission spectrum, and a high quantum yield. Compared with conventional phosphors, they form a point-to-point rapid energy transfer channel in the ABS matrix. The incident light is efficiently absorbed and quickly transferred by quantum dots, which improves the transmittance. At the same time, the highly single emission wavelength produces a more uniform scattering, with a haze of more than 98% and a color point of less than 0.005, achieving high optical performance that ordinary dyes cannot achieve.
[0065] 3. The chemical synergistic effect between the additives achieves long-term weathering stability. The antioxidant BHT removes polymer free radicals, and the light stabilizer HALS-770 neutralizes singlet oxygen. The two synergistically inhibit photo-oxidative degradation; UV-928 absorbs short-wave ultraviolet rays, and OB-1 absorbs long-wave ultraviolet rays. The superposition covers a wider spectrum, significantly delaying the photodegradation of quantum dots and ABS matrix. After accelerated aging tests, the service life is extended from 500h in the comparative example to more than 1200h. In addition, the additive content is low, which ensures the light transmittance of the system.
[0066] 4. The cohesion-isolation dual effect of the three-layer co-extrusion structure improves the durability of quantum dot performance. The middle layer is embedded with high-concentration quantum dots, which is conducive to energy transfer between quantum dots. The upper and lower layers contain silicone, which isolates external water vapor, oxygen, etc. while maintaining hardness and gloss, inhibiting the oxidative inactivation of quantum dots. And all three layers contain additives to form a three-dimensional protection. After aging for more than 1000 hours, the transmittance, haze and other properties decay by less than 5%, and the color points are almost unchanged, achieving a balance between quantum dot performance and service life.
[0067] In summary, the present invention significantly improves the mechanical strength, thermal stability and weather resistance while ensuring the excellent optical properties of the quantum dot diffusion plate through the interface capacity expansion of the ABS matrix and the surface modified quantum dots, the rapid energy transfer of the quantum dots, the chemical synergy of the additives and the cohesion-isolation dual effects of the three-layer co-extrusion structure, and the performance attenuation is small and the service life is long. This is unattainable for ordinary GPPS-based or dye-based diffusion plates. In addition, the present invention has a low dosage of additives, a simple process, and a low production cost, and has strong practicality and industrialization prospects.
[0068] The above description is only an embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent substitution, improvement, etc. made within the spirit and principle of the present invention should be included in the scope of the claims of the present invention.
Claims
1. An ABS quantum dot diffusion plate, characterized in that: The diffusion plate is composed of an ABS resin matrix, quantum dots, and additives, and includes an upper layer, a middle layer, and a lower layer, wherein: The intermediate layer material components include the following raw materials in parts by weight: 100 parts of ABS resin, 0.01-1 parts of quantum dots, 0.1-2 parts of antioxidants, 0.1-2 parts of ultraviolet absorbers, 0.1-2 parts of light stabilizers, 0.1-1 parts of mineral oils, and 0.01-1 parts of brighteners; The upper layer and the lower layer material components include the following raw materials in parts by weight: 100 parts of ABS resin, 0.01-1 parts of silicone resin, 0.1-2 parts of antioxidant, 0.1-2 parts of ultraviolet absorber, 0.1-2 parts of light stabilizer, 0.1-1 parts of mineral oil, and 0.01-1 parts of brightener; The quantum dots are CdSe quantum dots; The antioxidant is 2,6-di-tert-butyl-p-cresol; The ultraviolet absorber is UV-928; The light stabilizer is a composite hindered amine light stabilizer 770; The mineral oil is paraffin mineral oil; The brightening agent OB-1; The silicone resin is polydimethylsiloxane.
2. The method for preparing an ABS quantum dot diffusion plate according to claim 1, characterized in that: The following steps are involved: (1) Put the components of the middle layer and the upper and lower layers into a high-speed mixer according to the formula, and pre-mix them at a speed of 100-200 rpm for 5-15 minutes to obtain a middle layer mixture and an upper and lower layer mixture; (2) adding the intermediate layer mixture into a twin-screw extruder, extruding, cooling, and pelletizing at a temperature of 190-220° C. and a rotation speed of 30-50 rpm to obtain an intermediate layer masterbatch; (3) adding the upper layer mixture into a twin-screw extruder, extruding, cooling, and pelletizing at a temperature of 190-220° C. and a rotation speed of 30-50 rpm to obtain an upper layer masterbatch; the lower layer masterbatch is obtained by the same method; (4) The middle layer masterbatch, the upper layer masterbatch and the lower layer masterbatch are added into three single screw extruders at a weight ratio of 50-80:10-20:10-20, and extruded through a three-layer co-extrusion die head at an extrusion temperature of 200-240°C and a screw speed of 20-60rpm to form a sheet, which is stretched and shaped by a traction roller and cut to obtain an ABS quantum dot diffusion plate, wherein the thickness of the middle layer is 0.2-3mm, and the thickness of the upper and lower layers is 0.1-0.5mm.
Citation Information
Patent Citations
ABS material and preparation method thereof
CN108641275A
Novel quantum dot body light guide plate backlight module structure and preparation method thereof
CN108775541A
Quantum dot diffusion plate and preparation method thereof
CN114895492A
ABS (Acrylonitrile Butadiene Styrene) foaming diffusion plate and preparation method thereof
CN116769272A